Ultimate Outpouring of the Holy Spirit at Final Pentecost (Schema Pentecost – Pentecost on Going – Final Pentecost) - Budiatmaja , Rudy; Lamsir, Seno; Obaja , Christian; Saputra , Sony; Hutahaean, Hasahatan (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This study delves deeply into the urgent necessity for a revitalization of spiritual fervour within modern-day congregations, especially among Christians who have witnessed a decline or stagnation in their faith journeys. It meticulously examines the adverse repercussions of spiritual complacency, which not only precipitates moral decay but also compromises the church’s ability to fulfil its divine mandate effectively. Utilising a qualitative analysis firmly grounded in biblical precepts, the research thoroughly investigates the phenomenon known as the “third Pentecost,” underscoring the enduring importance of the Holy Spirit’s outpouring in reinvigorating the church. Also, employing a critical theological lens, the researchers methodically dissect the theological ramifications of the “third Pentecost” movement, juxtaposing its tenets with canonical scripture and historical perspectives. The study meticulously scrutinises the subjective nature of personal spiritual encounters and their potential influence on doctrinal fidelity, particularly in relation to the interpretation of Joel 2 and the realisation of Pentecost as chronicled in the Acts of the Apostles. Ultimately, the research underscores the perpetual relevance of the Holy Spirit’s divine manifestation, affirming its ongoing presence and anticipating its broader and more profound impact within contemporary spiritual revival movements.